La ville à l’écran : esthétique du spectaculaire et du tentaculaire dans Metropolis de Fritz Lang et Brazil de Terry Gilliam - Raphaëlle Costa de Beauregard (Anglophonia)
This paper addresses the city as a cultural construct in Metropolis (Fritz Lang, 1928) and Brazil (Terry Gilliam, 1985): first as a dream space for the development of futurist architecture, then as a privileged screen-space for chiaroscuro and the German expressionist context, and its transposition in Technicolor, and third as the locus for an irretrievable metamorphosis of the human species, particularly in the depiction of Woman as a "femme fatale".